Legal Legislation and Freedom of Expression / Historical Approach - AI-shimari, Rasheed Hussain (ALBAHITH ALALAMI, 2015)
Freedom of opinion and expression occupy the first place among the concerns of countries and international organizations. And it is also the basis of contemporary freedom because it is the foundation for achieving freedom in other fields such as politics, economics, education, etc.. The constitutions of the state have ensured that almost the entire freedom to express an opinion in all its forms either orally or writing or images of expressions, but these freedoms are identified within the law. Most countries announced their commitment to the international conventions and texts issued by international and regional organization like the Universal Declaration of Human Rights in 1948, and the International Covenant on Civil and Political Rights which have been adopted by the United Nations Freedom of opinion and expression occupies the first place among the concerns of countries and international organizations. And it is also the basis of contemporary freedom because it is the foundation for achieving freedom in other fields such as politics, economics, education, etc.. The constitutions of the state have ensured that almost the entire freedom to express an opinion in all its forms either orally or writing or images of expressions, but these freedoms are identified within the law. Most countries announced their commitment to the international conventions and texts issued by international and regional organization like the Universal Declaration of Human Rights in 1948, and the International Covenant on Civil and Political Rights which have been adopted by the United Nations The freedom of media has got a great importance because it is the most effective way in spreading the views of interests to communities, their aspirations, their rights, and to ensure them to communicate with each other. As well as it allows multiple sources through diversity in the dissemination of information. This way will help individuals ensuring that they verify the validity of the facts and make their own opinion on the events objectively. The freedom of expression has coupled with the right of access to information and its dissemination but these freedoms include duties and responsibilities. Therefore, it is forced to subdue this right for a number of legal proceedings, conditions, restrictions, specific penalties in the law as this is necessary in any democratic society in order to protect homeland and its safety, crime prevention, respect other’s rights and prevent the deployment of private secrets So, this research represents a simple effort to highlight the most important legislative aspects of some Arab constitutions that guarantee freedom of expression. And it necessitated the need to search some of the texts cited in the constitutions of Arab and foreign countries; we found how everyone agreed on freedom of expression and opinion and access to information and its circulation. Then, their freedoms have been bound with materials of the constitution to prevent the disclosure of information in many cases such as wars and crises